Inconsistent using FLOOD and Flooding Development of EPA SWMM for Assessing Flood Occurrences in Vulnerable Urban Watershed Considering Extreme Rainfall Events - Samia Alam; Md. Asifur Rahman (Journal of the Civil Engineering Forum, 2023)
Urban flood, commonly known as urban water congestion, is a type of water hazard that poses significant challenges for urban residents and water management experts. Chittagong, an essential economic hub in Bangladesh, renowned for its role as a port city, comprises a diverse range of land use, including residential, industrial, and commercial sectors. The Chaktai canal, an important element of Chittagong drainage system, is connected to the Karnaphuli river, playing a vital role in managing drainage by handling a substantial portion of the city water. Therefore, this research evaluated the operational efficiency of a specific drainage network under the influence of altered rainfall events using the Storm Water Management Model (SWMM). Using ArcGIS 10.4, the land use pattern of the area was researched, incorporating data from field surveys and secondary sources. SWMM 5.1 integrated watershed data, and further simulation was carried out to estimate runoff in various sub-catchments and drainage network limitations during heavy rain. During the intense monsoon period, the tool determined the average runoff depth, considering backwater effects and robust tidal surges, resulting in a depth of 3.3m compared to 2.6m in the dry season. This research evaluated the influence of impervious land use changes on urban drainage systems. While meteorological factors alone render drainage network sufficient in dry periods, the outfall shows vulnerability during the rainy season, with an allowance of only 0.7m, jeopardizing the catchment through flood. It contributed a schematic sub-catchment representation, emphasizing that flood events depend on volume runoff and peak flow in urban drainage system. SWMM model was used to illustrate the catchment surface runoff and interconnected node depths via conduits, as well as the current catchment scenario comprehensively.